2006
DOI: 10.1149/1.2205179
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Thin Iron Oxide Films on Si(100) by MOCVD

Abstract: The deposition of thin iron oxide films on Si͑100͒ by metallorganic chemical vapor deposition at 55 mbar was systematically studied as a function of temperature between 673 and 1023 K. Ferrocene and oxygen were used as precursors. The growth rate was measured as a function of temperature and the films were characterized by X-ray diffraction ͑XRD͒, Auger electron spectroscopy, energy dispersive X-ray analysis, and scanning electron microscopy. The change from the kinetically controlled regime to the transport c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Pflitsch et al obtained an activation energy of about 75 kJ/mol from iron oxide deposition experiments using ferrocene. 38 The growth rates in the second regime ͑i.e., higher than 500°C͒ were almost temperature-independent. This indicated that the deposition in this regime is mass transfer controlled.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pflitsch et al obtained an activation energy of about 75 kJ/mol from iron oxide deposition experiments using ferrocene. 38 The growth rates in the second regime ͑i.e., higher than 500°C͒ were almost temperature-independent. This indicated that the deposition in this regime is mass transfer controlled.…”
Section: Resultsmentioning
confidence: 99%
“…19 Pflitsch et al observed growth rates ranging from 35 to 120 nm/min using ferrocene and oxygen at a pressure of 55 mbar and temperature in the range of 400-750°C. 38 They studied the temperature dependence of film growth and reported three growth regimes: ͑i͒ below 450°C the rate was in the surface reaction-controlled regime, ͑ii͒ between 450 and 600°C the rate was in the diffusion-controlled regime, and ͑iii͒ above 600°C the growth rate decreased. Deposition rates in the present study using n-butylferrocene and oxygen range from about 4 nm/min at 400°C ͑in the kinetics-controlled regime͒ to 50 nm/min at temperatures above 500°C ͑in the mass transfer-controlled regime͒.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the most powerful techniques suitable for the formation of stoichiometric and microstructured thin films (Park et al 2006), chemical vapour deposition has been employed for fabrication of iron oxide thin films from different precursors (Shalini et al 2003 and the references therein;Mathur et al 2006;Park et al 2006;Pflitsch et al 2006;Lee et al 2007). The overall motivation for the present work has been to conduct analytical studies to provide stability windows in the CVD process employing metalorganic precursors, corresponding to the experimental realization of specific iron oxide phases.…”
Section: Introductionmentioning
confidence: 99%
“…2 Because of difference for application depending on their chemical composition and structure, it is important to control their shape. Many oxide materials have been used extensively in the form of thin films because the applications involve microdevices that require materials fabricated on micron or submicron scales.…”
Section: Introductionmentioning
confidence: 99%